2006
DOI: 10.1007/s10654-006-9052-7
|View full text |Cite
|
Sign up to set email alerts
|

Suicide among Indigenous Sami in Arctic Norway, 1970–1998

Abstract: Suicide mortality was examined between 1970 and 1998 in a cohort of 19,801 persons categorized as indigenous Sami in Arctic Norway. Standardized mortality ratios (SMR) were calculated using the suicide rates of the rural population of Arctic Norway as reference. There was a significant moderate increased risk for suicide among indigenous Sami (SMR = 1.27, 95% Confidence interval (CI): 1.02-1.56). In the study period, 89 suicides occurred in the cohort (70 men and 19 women) with increased suicide mortality both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 27 publications
5
66
0
7
Order By: Relevance
“…Moreover, the results of these studies are ambiguous [12], probably due to differences in problem formulation and study design [12,17]. Further, the lack of differences in mental health problems between Sami and Norwegians, as presented in certain earlier papers [13,17], may be due to overlooked within-group differences in the Sami population. For instance, some Sami subgroups may be less vulnerable to mental health problems due to protective factors at an individual, family and/or community level [28,51].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results of these studies are ambiguous [12], probably due to differences in problem formulation and study design [12,17]. Further, the lack of differences in mental health problems between Sami and Norwegians, as presented in certain earlier papers [13,17], may be due to overlooked within-group differences in the Sami population. For instance, some Sami subgroups may be less vulnerable to mental health problems due to protective factors at an individual, family and/or community level [28,51].…”
Section: Discussionmentioning
confidence: 99%
“…In connection with the national census in 1970, a survey of Sami ancestry was performed in preselected census tracts in the 3 northernmost counties of Norway: Nordland, Troms and Finnmark (see Aubert, 1978 Table I. A more detailed description of the sample and the procedure in Study I are provided elsewhere (2).…”
Section: Study Imentioning
confidence: 99%
“…Such discriminatory public policies have justified State expropriation of pastoralist lands for sedentary agriculture, resource extraction or infrastructure development, national parks or nature reserves, with devastating effects on both the environment and on the pastoralist peoples themselves. These negative approaches are beginning to provide some lessons: 61 Studies from Africa have in fact shown that pastoral systems are two to 10 times more productive than ranching alternatives in the drylands. "Despite gross underinvestment and neglect, both in the production system and in the producers themselves, pastoralism continues to contribute healthily to national economies and export earnings".…”
Section: Pastoralistsmentioning
confidence: 99%
“…It is nevertheless very likely that a great number of pastoralists will have to deal with increasingly dry and less fertile lands. In addition to changing rainfall patterns, other major effects include biodiversity shifts, changing wind patterns, more frequent floods and droughts, heat waves 61 Nori, Taylor and Sensi (2008) 62 Hatfield and Davies (2006), 5 pastoralism is practised on 25 per cent of the global land area and tropical cyclones. Therefore, it is essential that their primary coping tool-mobility-be respected rather than restricted.…”
Section: Pastoralistsmentioning
confidence: 99%
See 1 more Smart Citation